(untitled) (Journal of Laboratory Animal Science, 2022)
Post approval monitoring (PAM) is an internal process for the ongoing research activities of approved protocols adopted by the institution. The primary goals are to ensure research methodology is conducted in accordance with the approval, evaluation of animal manipulations to reduce pain and distress, assessment of surgical procedures and post-operative care, to provide timely feedback to refine procedures and understand the proficiency of individuals on specific techniques of the species involved in experiments. The best approach should be collegial and facilitative of informed observations that provide an oversight of experiments conducted by principal investigators (PI’s) along with other researchers listed in the protocol. In general, institutions can efficiently monitor this PAM process through any researcher/veterinarian/ coordinator who have considerable research experience as well as involved in the protocol review process or may be part of ethical committee for effective oversight of the animal care program. The proactive approach is fostering scientific conversation with research personnel and builds relationship by adhering institutional policies on animal research which in turn creates a positive culture of compliance throughout the institution. Collectively, PAM observation is ensuring the quality, research integrity, compliance with regulations and well-being of animals that eventually provides an opportunity for identifying educational competency, training based on observation categories and enabling the systematic communication process between animal care technicians, veterinarians, investigators, ethics committee and management for better compliance and humane care and use of animals for research.